Dogme Teaching Approach as A Revolutionary Teaching Philosophy against Textbook Teaching Based Approach (Al-Farooq Journal of Sciences, 2026)
Teaching English language in its traditional mode is excessively based on textbook which represents a useful resource for both teachers and learners. Nonetheless, it has some drawbacks such as the content may not be relevant , inauthenticity,  regarding it  as the sole source of information, not considering the students’ background knowledge  and tendency of over reliant on textbooks .  Dogme is a communicative approach to language teaching which involves free published textbook class and interactive conversational communication among learners. It is evolved in 2011 by Scott Thornbury and Luke Meddings who design it as free instructors from a dependence on materials and technology and work with nothing more than the interests of the people in the room. It is a teaching philosophy which goes beyond the standard pedagogical methods and it is a textbook free zone. It has various principles interactivity, engagement, dialogic processes, scaffolded conversations, affordances, empowerment, relevance and critical use. The main precepts of Dogme are conversation-driven teaching, materials light approach and emergent language. It is compatible with reflective teaching and it recognizes the legitimacy of learners needs and expectations.
Keywords: Dogme teaching, textbook , scaffolded , interactivity , unplugged teaching